1987
DOI: 10.1111/j.1365-2362.1987.tb01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Captopril enhances insulin responsiveness of forearm muscle tissue in non‐insulin‐dependent diabetes mellitus

Abstract: Bradykinin infusion has been shown to improve glucose metabolism in non-insulin-dependent diabetic subjects (NIDD). Therefore, we tested the following hypothesis: inhibition of Kininase II, the bradykinin (BK) degrading enzyme, by captopril may also improve glucose metabolism in NIDD. Immediate effects of captopril on total body and peripheral glucose disposal were examined in five normotensive, normal weight NIDD and compared with five NIDD control subjects, well matched for age, weight and degree of fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
2
5

Year Published

1988
1988
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 46 publications
6
57
2
5
Order By: Relevance
“…In addition to the amelioration of insulin secretion through the increased islet blood flow induced by an ACE inhibitor, as seen in this study, the blockade of the RAS during the development of diabetes has been attributed to improvements in peripheral insulin sensitivity and b-cell dysfunction (30,31). ACE inhibitors have been shown to improve whole-body and skeletal muscle insulin resistance in hypertensive subjects with or without type 2 diabetes (32)(33)(34)(35)(36)(37)(38)(39)(40). The reduction of angiotensin II-mediated vascular resistance by ACE inhibition may improve insulin-stimulated glucose transport activity in skeletal muscle (41).…”
Section: Discussionmentioning
confidence: 86%
“…In addition to the amelioration of insulin secretion through the increased islet blood flow induced by an ACE inhibitor, as seen in this study, the blockade of the RAS during the development of diabetes has been attributed to improvements in peripheral insulin sensitivity and b-cell dysfunction (30,31). ACE inhibitors have been shown to improve whole-body and skeletal muscle insulin resistance in hypertensive subjects with or without type 2 diabetes (32)(33)(34)(35)(36)(37)(38)(39)(40). The reduction of angiotensin II-mediated vascular resistance by ACE inhibition may improve insulin-stimulated glucose transport activity in skeletal muscle (41).…”
Section: Discussionmentioning
confidence: 86%
“…2). Increased activity of the renin angiotensin system has been associated with obesity and glucose intolerance, and prospective epidemiological studies have reported that blocking the system using either ACE inhibitors or ARBs has been shown to reduce the incidence of diabetes (27,28,29,30) and both ACE-inhibitors and ARBs may improve insulin action to different extents (31,32) as well as insulin secretion (33). Accordingly, it may be considered biologically plausible that bioactive peptides in the Cardi04 yogurt inhibiting ACE may reduce plasma glucose levels in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the beneficial effects of the use of ACEi and AT 1 blockers in patients with type 2 diabetes has been known for quite some time [43][44][45]. The overactivity of the RAS is likely to impair insulin signaling and contribute to the insulin resistance observed in essential hypertension [7].…”
Section: The Cross-talk At the Extracellular Levelmentioning
confidence: 99%